Haplotype Diversity of Swamp Buffalo and River Buffalo Based on Cytochrome B Gene: A Study of Meta-Analysis - F. Saputra; A. Anggraeni; A. B. L. Ishak; A. Hafid; M. Rusdin; C. Sumantri (Faculty of Animal Science, Bogor Agricultural University, 2021)
Buffalo (Bubalus bubalis) is well known as a domesticated buffalo in Asia. The genetic diversity of buffaloes in Asia needs to be studied to ensure a proper breeding program. A meta-analysis study on the cytochrome b gene of the mitochondrial genome from various published data was conducted to evaluate genetic variation and haplo-geography of Asian buffaloes. A meta-analysis is used to provide a comprehensive view of the data. A total of 1369 swamp buffaloes Cytochrome B sequences (from Indonesia (79), Bangladesh (98), China (909), India (4), Laos (96), Taiwan (29), Thailand (54), and Vietnam (100)) and 91 river buffaloes (from China (42), Nepal (42), and Pakistan (7)) were used in this study. Cytochrome B sequences (678 bp) of Syncerus caffer, Bubalus arnee, Bubalus depressicornis, Bubalus quarlesi, Bubalus mindorensis, swamp buffalo, and river buffalo were determined for their haplotypes using DnaSP v6 program. Haplotypes were analyzed by Principal Coordinate Analysis (PCoA) using Adegenet Package and Hierarchical Clustering on Principal Components (HCPC) methods using Factoextra and FactoMineR Package in R-4.0.0 program. Bayesian analysis of genetic differentiation was implemented in BAPS 6.0. Furthermore, we found 56 haplotypes for swamp buffaloes in eight Asian countries and 5 haplotypes for river buffaloes in Pakistan. We also found 5 haplotypes for outgroup (B. arnee, S. caffer, B. depressicornis, B. quarlesi, B. mindorensis). Therefore, we found 66 haplotypes in total with outgroup sequences. Based on the PCoA results, three clusters were found. However, the HCPC found eight clusters. Based on HCPC, countries in East and South Asia have four maternal lineages. This is evidence that buffalo domestication has first occurred in East-South Asia. In conclusion, we found four maternal lineages of swamp buffalo and two maternal lineages of river buffalo from ten countries. We also found one maternal lineage for Syncerus caffer and one maternal lineage for B. depressicornis, B. quarlesi, and B. mindorensis.